HR and marketing (traditional and digital) practices of Pechas Game Studios - Adib, Mostofa Rafat Mahdi (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.